Fuel prices and economic activity: time and frequency analysis for selected European countries - Geise, Andrzej; Piłatowska, Mariola (Technological and Economic Development of Economy, 2025)
The effects of fuel prices on economic activity are still being investigated, as oil and gas are critical inputs in the production process. This study examines the relationship between fuel prices and macroeconomic aggregates both in the time domain and frequency domain in three selected countries of Germany and Poland as net oil importers and Norway as a net oil exporter for the period 1995Q1–2021Q3. The causal relationships between these macroeconomic variables are first examined using a conventional Granger causality test for the time domain and then the Breiutung–Candelon test based on the vector autoregression model for the frequency domain, which are estimated separately for the long-term, business cycle, and short-term components obtained by applying the boosted Hodrick–Prescott filter. This study demonstrates that the predictability of fuel prices for macroeconomic aggregates differs across various frequencies. Although the patterns of causality differ across countries depending on whether it is oil-importing or oil-exporting and the level of economic development and energy mix, this relationship is found to be important for slowly and fast fluctuating components but to different degrees in each country.First published online 15 April 2025